Deep-sea living (stained) benthic foraminifera from the continental slope and São Paulo Plateau, Santos Basin (SW Atlantic): ecological insights (Ocean and Coastal Research, 2024)
This study aimed to characterize the spatial distribution and composition of living Benthic Foraminifera (BF) and tocomprehend how environmental conditions (e.g., organic matter) can affect communities of these protozoa in thenorthern and southern sectors of the Santos Basin (SB), in the continental slope and São Paulo Plateau. In this context,23 stations (65 samples including replicates at each station) were collected between 400 and 2,400 m water depth.Multivariate analyses revealed that the ecological structure of the community changes mainly along the bathymetricgradients. Stations located between 400 and 700 m, both in northern and southern sectors, are characterized bythe presence of indicator species of high intensity of currents, such as Globocassidulina subglobosa and Trifarinabradyi. These stations are also mainly marked by the occurrence of Epistominella exigua, a phytodetritivore species.The stations at 1,000 and 1,300 m depth, in both sectors, are characterized by high accumulation of organic matterin the sediments, which favors the development of agglutinated foraminifera species, such as those of the genusReophax. Finally, the lower slope and the São Paulo Plateau, in both sectors, are oligotrophic regions, with pulses oflabile organic carbon, probably low current velocities and the presence of Alabaminella weddellensis. The quantityand quality of food, which are closely related to hydro-sedimentary dynamics and bentho-pelagic coupling in theslope and São Paulo Plateau, are the main factors that influence the distribution of living BF assemblages in the SB.